2006
DOI: 10.1080/00071660500475574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formic acid on performance, digestibility, intestinal histomorphology and plasma metabolite levels of broiler chickens

Abstract: 1. The effect of dietary formic acid on performance, digestibility, intestinal histomorphology and plasma metabolite levels of broiler chickens was studied. 2. An experiment with 120 Ross male broiler chickens was conducted from 1 to 42 d of age at the laboratory. There were 4 treatment groups: control (C), 10 mg/kg feed avilamycin (AV) and formic acid at two concentrations, 5 and 10 g/kg feed (FA5 and FA10, respectively). 3. No differences in weight gain, feed intake or feed conversion ratio were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
88
5
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(127 citation statements)
references
References 19 publications
23
88
5
11
Order By: Relevance
“…In a study by Timmerman et al (2006), it was reported that the positive effects of probiotics on highperformance broilers were lower than in low-performing birds. Houshmand et al (2012), in agreement with the results of Hernandez et al (2006), did not find positive effects of organic acid (formic acid) on performance. In this study, body weight gain was significantly affected by organic acid in the starter phase.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In a study by Timmerman et al (2006), it was reported that the positive effects of probiotics on highperformance broilers were lower than in low-performing birds. Houshmand et al (2012), in agreement with the results of Hernandez et al (2006), did not find positive effects of organic acid (formic acid) on performance. In this study, body weight gain was significantly affected by organic acid in the starter phase.…”
Section: Resultssupporting
confidence: 81%
“…Xu et al (2003) reported that decreased crypts depth may lead to poor nutrient absorption, increased secretion in the gastrointestinal tract and lower performance. Similar results were observed by Hernandez et al (2006) with formic acid, which increased the crypt depth of the small intestine. Garcia et al (2007) observed improved villus height and significant increase in crypt depth, but villus surface area was not influenced.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This is probably because of the strong buffering action of the poultry gastrointestinal tract. This result supports the previous findings reported by Izat et al 1990 andHernandez et al 2006, indicative of an antimicrobial action of the OAB in the upper alimentary tract. Therefore, the antimicrobial action of OAB in the gizzard might have reduced the number of the Enterobacteriaceae and increased the numbers of Lactobacillus in the small intestine as a compensatory mechanism.…”
Section: Intestinal Microbial Populationsupporting
confidence: 83%
“…Additionally, undissociated organic acids can penetrate the lipid membrane of the bacterial cell and decrease intracellular pH, which leads to death (Ricke, 2003), in addition to stimulating pancreatic secretion and providing better intestinal villus integrity (Dibner & Buttin, 2002). However, there are conflicting results regarding the use of acidifiers in poultry and, according to Hernández et al (2006), these effects depend on the chemical form of the acid, pKa values, bacterial species to be destroyed, animal species and the site of action of acids.…”
Section: Introductionmentioning
confidence: 99%